A Review: Melia azedarach L. as a Potent Anticancer Drug Martha Ervina1,2, - Ervina, Martha; S, Sukardiman (Pharmacognosy Reviews)
Chinaberry (Melia azedarach L., Meliaceae), a Mahogany family usually used as high quality timber, is native to Asia but now is found in other parts of tropical world continent. The leaves, fruits, bark, seed and root are use in traditional medicine and it has been shown to various pharmacological activities like antifungal, anti-malarial, antibacterial, hepatoprotective, anti-oxidant, anti-fertility, anthelmintic, antipyretic and cytotoxic. A review to its phytochemical and anticancer properties of M. azedarach and its sub species or varieties as an effort to analyze the literature on its developing used as anticancer agent. As results of literatures review indicates that fruit, bark, leaves, pulp and seed of Melia azedarach L. showed various in vitro cytotoxic activities in cancer cell lines, such as human colorectal carcinoma (HT-29), breast cancer (MCF-7, SK-BR-3), cervix hepatoma (HepG-2, SMMC-7721 and Hep3B), kidney epithelial cell (MDBK), human lung adenocarcinoma epithelial cell (A549), non-small cell lung cancer (H460), human lymphoblast lung (U937), human cancer promyelocytic leukemia (HL-60), AZ521 (stomach), human colon cancer (SW480), murine colorectal adenocarcinoma cell (CT26), human oral cancer cell (KB), human prostate cancer (PC3), liver (BEL7404), CNS (SH-SY5Y, U251, SF539), B16F10 mouse melanoma cell line; and showed various in vivo to adenocarsinoma mammary in C3H mice and mouse hepatocellular carcinoma H22 cells to BALB/c mice. Previous results suggested that cytotoxic organic compounds of Melia azedarach L. were supposed of flavonoids, triterpenoids (tirucallane), limonoids (meliarachin, meliatoxin B1, trichilin H, and toosendanin), steroids, and organic acids content compounds.
Keywords: Anticancer; cytotoxic; Melia azedarach; Melia; triterpenoids; limonoid